2002
DOI: 10.1001/archpsyc.59.9.809
|View full text |Cite
|
Sign up to set email alerts
|

Visual Fixation Patterns During Viewing of Naturalistic Social Situations as Predictors of Social Competence in Individuals With Autism

Abstract: When viewing naturalistic social situations, individuals with autism demonstrate abnormal patterns of social visual pursuit consistent with reduced salience of eyes and increased salience of mouths, bodies, and objects. Fixation times on mouths and objects but not on eyes are strong predictors of degree of social competence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

107
1,400
35
46

Year Published

2006
2006
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 1,721 publications
(1,641 citation statements)
references
References 48 publications
107
1,400
35
46
Order By: Relevance
“…Such an approach fits with several eye-tracking studies that have similarly observed a particular focus on the mouth (Jones, Carr, & Klin, 2008; Klin, Jones, Schultz, Volkmar, & Cohen, 2002) and could reflect several different mechanisms. A bias toward the mouth (often also associated with a bias away from the eyes) could be associated with atypical communication in the condition (Langdell, 1978), an aversion to the socially intimidating eye region (Tanaka & Sung, 2013) or a failure to appreciate the utility of this information (Itier & Batty, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Such an approach fits with several eye-tracking studies that have similarly observed a particular focus on the mouth (Jones, Carr, & Klin, 2008; Klin, Jones, Schultz, Volkmar, & Cohen, 2002) and could reflect several different mechanisms. A bias toward the mouth (often also associated with a bias away from the eyes) could be associated with atypical communication in the condition (Langdell, 1978), an aversion to the socially intimidating eye region (Tanaka & Sung, 2013) or a failure to appreciate the utility of this information (Itier & Batty, 2009).…”
Section: Discussionsupporting
confidence: 76%
“…Because children with ASD may lack the motivation to participate in activities in which social skills are typically forged, the resulting relatively impoverished social environment may further compound the social impairment caused by low social motivation, and further negatively influence the development of social cognition and language skills [553,554]. Consistent with this model, very young children with ASD display decreased orienting to social stimuli [550,555], and atypical social orienting has been shown to predict decreased social competence in adolescents and young adults with ASDs [556]. There is also evidence that social motivation remains impaired in individuals with ASD despite growth in other areas of cognitive development.…”
Section: Reviewmentioning
confidence: 99%
“…Eye gaze appears to rely in part on amygdala function (Adolphs et al, 2005). Studies of eye gaze in autism have reported discrepancies for dynamic social stimuli (Klin et al, 2002;Speer et al, 2007), although eye gaze for static photos is more intact (Pelphrey et al, 2002;van der Geest et al, 2002).…”
Section: Introductionmentioning
confidence: 99%